Self‐Healing Cs3Bi2Br3I6 Perovskite Wafers for X‐Ray Detection. (21st August 2021) - Daum, Manuel; Deumel, Sarah; Sytnyk, Mykhailo; Afify, Hany A.; Hock, Rainer; Eigen, Andreas; Zhao, Baolin; Halik, Marus; These, Albert; Matt, Gebhard J.; Brabec, Christoph J.; Tedde, Sandro F.; et al.
Abstract: Self‐healing of defects imposed by external stimuli such as high energy radiation is a possibility to sustain the operational lifetime of electronic devices such as radiation detectors. Cs3 Bi2 Br3 I6 polycrystalline wafers are introduced here as novel X‐ray detector material, which not only guarantees a high X‐ray stopping power due to its composition with elements with high atomic numbers, but also outperforms other Bi‐based semiconductors in respect to detector parameters such as detection limit, transient behavior, or dark current. The polycrystalline wafers represent a size scalable technology suitable for future integration in imager devices for medical applications. Most astonishingly, aging of these wafer‐based devices results in an overall improvement of the detector performance—dark currents are reduced, photocurrents are increased, and one of the most problematic properties of X‐ray detectors, the base line drift is reduced by orders of magnitude. These aging induced improvements indicate self‐healing effects which are shown to result from recrystallization. Optimized synthetic conditions also improve the as prepared X‐ray detectors; however, the aged device outperforms all others. Thus, self‐healing acts in Cs3 Bi2 Br3 I6 as an optimization tool, which is certainly not restricted to this single compound, it is expected to be beneficial also for many further polycrystalline ionic semiconductors. Abstract : Lead‐halide perovskites are appealing due to their facile fabrication and promising opto‐electronic properties. However, their toxicity and stability issues remain unsolved. As an alternative, Cs3 Bi2 Br3 I6 is presented here, tested for X‐ray detection. Surprisingly, the polycrystalline wafer devices are not only stable, but exhibit improved properties after long term aging, which may be attributed to the self‐healing of this material by recrystallization.